Creating charisma online: the role of digital presence in the formation of religious identity. Issue 1 (2nd January 2019) - Tee, Caroline
ABSTRACT: This article investigates the construction and transmission of charisma through online channels and its role in the formation of religious identities. Mindful of Max Weber's observation that charisma inhabits the relationship between a leader and his/her followers, I argue for a critical reappraisal of the theoretical model in the light of the ubiquity in the twenty-first century of new, virtual forms of social encounter. I focus my analysis on the Christian creationist movement in the United States and particularly on an influential leader called Ken Ham. Using digital ethnographic methods, I show how Ham constructs charisma online and how a virtual community forms itself around his charismatic claims. I illustrate how this virtual community intersects with offline worlds and suggest that the theme park attractions that Ham's organisation runs (Creation Museum, Ark Encounter) are imbued with deflected charisma by virtue of their association with his online avatar.